CATEGORY SHIFTS IN TRANSLATION: A CASE STUDY ON THE TRANSLATION OF ENGLISH COMPLEX NOUN PHRASES INTO INDONESIAN - Darso Donatus (Lingua Scientia, 2018)
This study aims at identifying the types of category shifts and explaining their occurrence in the translation of complex noun phrases from English into Indonesian in The Valley of Fear Novel. The data were collected using observation method which was supported by implementing note taking technique in order to find out, identify, and classify the data. The data were analyzed by applying the qualitative descriptive method. The theory applied in this study is the theory of translation proposed by Catford (1965) to identify the types of category shifts found and to explain their occurrence. The result shows that all types of category shifts proposed by Catford (1965) such as structure shift, class shift, intra-system shift, and unit shift are found in the translation. Structure shift occurs in the highest frequency of 339 cases or about 66,86% out of total 507 cases, class shift occurs 75 cases or 14,79 % out of total 507 cases, and intra-system shift occurs 48 cases or 9,46 % out of total 507 cases, and unit shift occurs 45 cases or 8,87 % out of total 507 cases. The occurrence of category shift is caused by the different characteristics of source language and target language.